Management of IFN-beta-induced flu-like symptoms with Chinese herbal medicine in a patient with multiple sclerosis: A case report. (February 2018) - Lee, Li-Wen; Lin, Hung-Jen; Huang, Sheng-Teng
Abstract: Objective: The purpose of this case report was to elucidate how Chinese herbal medicine (CHM) was used safely in this patient undergoing interferon beta (IFNβ-1a) treatment and was associated with reduction in the side effects the patient had experienced when using IFNβ-1a treatment alone. Clinical features and outcome: A 30-year-old man was diagnosed with MS in December 2014. For two years, he suffered from severe flu-like symptoms as side effects of IFNβ-1a treatment. He subsequently received treatment with Chinese herbal medicine. During a two-month period of treatment with CHM, the patient responded well, with most of the symptoms induced by IFNβ-1a ameliorated. The fever subsided. Incidence rates of dizziness and headaches were reduced. The health condition compared to the prior year increased by 50%. According to CCMQ and SF-36 assessments, CHM had the beneficial effects of recovering the yin-yang balance, harmonizing the qi, and regulating the blood state; essentially, improving the patient's comfort level and quality of life. Conclusions: IFNβ-1a injections will damage qi and cause blood stasis in MS patients, thereby causing various side effects and weakening the body's immune system. Bu-Zhong-Yi-Qi-Tang, associated with Salvia miltiorrhiza, Ligusticum chuanxiong, Angelica dahurica and Polygonum multiflorum Thunb., is an effective prescription to ameliorate such symptoms and signs in patients with MS.